2021
DOI: 10.1101/2021.02.26.432961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted replacement of full-length CFTR in human airway stem cells by CRISPR/Cas9 for pan-mutation correction in the endogenous locus

Abstract: Cystic fibrosis (CF) is a monogenic disease caused by impaired production and/or function of the cystic fibrosis transmembrane conductance regulator (CFTR) protein. Although we have previously shown correction of the most common pathogenic mutation, there are many other pathogenic mutations throughout the CF gene. An autologous airway stem cell therapy in which the CFTR cDNA is precisely inserted into the CFTR locus may enable the development of a durable cure for almost all CF patients, irrespective of the ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Current gene integration approaches primarily rely on nuclease-directed DNA double-stranded breaks (DSBs) to direct cellular DNA repair pathways, such as homologous recombination (HR). Despite important advances in optimizing HR in specific contexts 3,4 , these approaches generally suffer from low insertion efficiency, high indel rates and cargo size limitations, with limited success for cargoes larger than 1 kb [5][6][7] . Furthermore, HR-based gene editing is not feasible in post-mitotic cells, and formation of DSBs is toxic in many primary cell types, leading to undesired deletions, complex rearrangements 8 or activation of…”
mentioning
confidence: 99%
“…Current gene integration approaches primarily rely on nuclease-directed DNA double-stranded breaks (DSBs) to direct cellular DNA repair pathways, such as homologous recombination (HR). Despite important advances in optimizing HR in specific contexts 3,4 , these approaches generally suffer from low insertion efficiency, high indel rates and cargo size limitations, with limited success for cargoes larger than 1 kb [5][6][7] . Furthermore, HR-based gene editing is not feasible in post-mitotic cells, and formation of DSBs is toxic in many primary cell types, leading to undesired deletions, complex rearrangements 8 or activation of…”
mentioning
confidence: 99%
“…In fact, several studies reported the enrichment of p53-inactivating mutations following CRISPR-based editing in immortalized human cell lines with constitutive or inducibly expressed Cas9 when a subset of p53 mutant cells were spiked in 1,2 . In contrast, prior studies in human primary cells found that Cas9 RNP delivery did not introduce mutations in p53 or 129 other cancer-related genes (using the Stanford Solid Tumor Actionable Mutation Panel) 36,37 . Therefore, we developed a novel tumor suppressor/oncogene ultra-deep sequencing pipeline to determine whether editing and short-term ex vivo expansion leads to disruption and/or enrichment of cancer-associated variants when delivered in a clinically relevant context-i.e., when high-fidelity Cas9 15 is transiently delivered as RNP via electroporation to human primary HSPCs without subpopulations of cells with pre-existing tumorigenic variants.…”
Section: Discussionmentioning
confidence: 69%
“…This makes use of two consecutive HDR steps that first integrate one half of the gene and then the next half, hence overcoming the capacity limit for a single AAV, which potentially would enable a universal HDR approach to target all known DOCK8 mutations present in the reading frame ( Figure 5E ) ( Balakrishnan and Jayandharan, 2014 ). This approach has recently shown promise as a curative correction strategy for cystic fibrosis, which involves the large 4.4 kb CFTR ORF ( Vaidyanathan et al, 2021 ).…”
Section: Towards a Curative Crispr/cas9-based Gene Editing Approach F...mentioning
confidence: 99%